Pendidikan Hati Perspektif al-Ghaz?l? dalam Kitab Ihya’ Ul?m al-D?n - Muhammad Hasyim (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2017)
Al-Ghaz?l? in Sufism has had big influenced of his thought in the world. He was Syafi’i follower in fiqih law and Asy’ariyah in theology, when he was in Baghdad he hung out with many mazhabs. Ihya’ Ul?m al-D?n is outlined with sharp thought method. The discussion is divided to systematic parts. It combined outward and inner fiqh, in explaining the difficult terms, this book uses tamstil. Al Ghazali has written heart diseases and its medicine. It also inserted many advantage stories as refreshing phase. Heart education is the soul controlling process. This soul consequently is able to encourage the physical activity in daily life appropriate with syari’ah of Allah through riyadhoh, fasting, praying or other worships. It also makes person becomes obidient people from birth to death, through many education and teaching and learning gradually, in which the learning peocess is parents and society responsibility toward a pious (shalih) person. The purpose of psychology according to Ghazali is forming pious or shalih people.